(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
الأسطورة الأوغاريتية بالوحدات المكونة لها هي عبارة عن رموز تستند إلى وحدات لغوية ، لها الدلالات المعجمية والرمزية ، فالألفاظ اللغوية فيها دينية تتوزعها الحقول الدلالية : الخير والشر ، والموت والحياة ، والخصب والجفاف ، والذكورة والأنوثة ، والعدوان والمصالحة ، والبطولة والضعف ، والغياب والحضور .... ولأن هذه الوحدات اللغوية لها الدلالات الرمزية ، للصراع بين الآلهة ، وللصفات الدينية لإل ، وبعل ، وعناة ..... ، ولغيرها من المواد الأسطورية ، فهذا البحث هو في جانب منه دراسة " اللغة الرمزية " في النص المدوَّن بالخط المسماري الأوغاريتي . مع دراسة في " العناصر المرئية " التي تدل على معان لغوية . أما الجانب الأخير فهو لتأثيل الألفاظ والظواهر اللغوية ( دراسة الأصول ) في اللغة العربية بالمقارنة مع مقابلاتها في اللغة الأوغاريتية . The Ugariti legend with its elements consists of symbols which are based on linguistic units that have lexical and symbolic signification. The lexical items are religious and distributed into the following semantic fields: Good and evil, death and life, fertility and dryness, masculinity and femininity, aggression and forgiveness, heroism and weakness, absence and presence. Since these linguistic units have symbolic indications for the conflict between the Gods, and for the religious characteristics of EL, Ba’al, and Anat and for other legendary elements, this study is, on the one hand, a study of the symbolic language in the text recorded in the Cuneiform Ugariti script, and it is also a study of the visual elements representing linguistic meanings. The final part is an Etymology of linguistic features in Arabic, in comparison with their counterparts in the Ugariti Language.